Efektivitas Komunikasi Pemasaran Melalui Media Sosial untuk Menumbuhkan Kesadaran Merek Ladang Lima - Dinda Satya Rani; Sri Tjondro Winarno; Eko Priyanto (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2021)
The purpose of this study is to analyze the marketing communications that have been carried out by PT ABA through social media to raise awareness of the Ladang Lima brand. The object of this research is Ladang Lima Instagram, with the sample being Ladang Lima Instagram followers. The research method used is descryptive quantitative with the Customer Response Index (CRI). The result of this research is the marketing communication carried out by the company through social media Instagram has been effective in growing brand awareness, with a CRI value of 43.25%, this is also supported through analysis of brand awareness at the top of the mind level, the first healthy food brand mentioned by the respondent with the most answers was Ladang Lima. PT ABA lost the most consumer responses in the intention to action stage on the CRI hierarchy of 20.67%, meaning that after seeing marketing communications through Ladang Lima's Instagram, many respondents had the intention to buy Ladang Lima products, but did not actually take the purchase action.